Variation in Oxytocin is Related to Variation in Affiliative Behavior in Monogamous, Pairbonded Tamarins - Snowdon, Charles T. (2010)
Oxytocin plays an important role in monogamous pairbonded female voles, but not in polygamous voles. Here we examined a socially-monogamous cooperatively breeding primate where both sexes share in parental care and territory defense for within species variation in behavior and female and male oxytocin levels in 14 pairs of cotton-top tamarins (Saguinus oedipus), In order to obtain a stable chronic assessment of hormones and behavior, we observed behavior and collected urinary hormonal samples across the tamarins’ three week ovulatory cycle. We found similar levels of urinary oxytocin in both sexes. However, basal urinary oxytocin levels varied ten-fold across pairs and pair-mates displayed similar oxytocin levels. Affiliative behavior (contact, grooming, sex) also varied greatly across the sample and explained more than half the variance in pair oxytocin levels. The variables accounting for variation in oxytocin levels differed by sex. Mutual contact and grooming explained most of the variance in female oxytocin levels whereas sexual behavior explained most of the variance in male oxytocin levels. The initiation of contact by males and solicitation of sex by females were related to increased levels of oxytocin in both. This study demonstrates within-species variation in oxytocin that is directly related to levels of affiliative and sexual behavior. However, different behavioral mechanisms influence oxytocin levels in males and females and a strong pair relationship (as indexed by high levels of oxytocin) may require the activation of appropriate mechanisms for both sexes.